Antibiotic production by an endophytic Streptomyces isolated from the medicinal plant Poikilospermum suaveolens - ALIMUDDIN ALI; MUHARRAM PASSITTA; HERLINA RANTE; ELLY WAHYUDIN; NANA JUNIARTI NATSIR DJIDE; ROLAND JANSEN POLITAN; ELYZA AIMAN NUR; SATORU SHIGENO; SATOSHI OHTE; KEISUKE KOBAYASHI; KANJI HOSODA; HIROSHI TOMODA; TAICHI OHSHIRO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Ali A, Passitta M, Rante H, Wahyudin E, Djide NJN, Politan RJ, Nur EA, Shigeno S, Ohte S, Kobayashi K, Hosoda K, Tomoda H, Ohshiro T. 2024. Antibiotic production by an endophytic Streptomyces isolated from the medicinal plant Poikilospermum suaveolens. Biodiversitas 25: 2221-2229. This study investigates the antibiotic production potential of endophytic actinomycetes isolated from Poikilospermum suaveolens plants. Samples were collected from various parts of the plant in karst ecosystems. Endophytic actinomycetes were cultured and screened for antimicrobial activity using agar diffusion and liquid microdilution methods. One of the 11 isolated strains exhibited significant antibiotic activity against clinically relevant organisms identified as belonging to the Streptomyces genus, specifically Streptomyces mirabilis strain NRRL ISP-5169. Submerged fermentation of this strain over 9 days showed strong antagonistic effects against Gram-positive bacteria. Spectroscopic analyses confirmed the presence of actinomycin D as the bioactive compound. This study provides on the previously unexplored potential of endophytic actinomycetes from P. suaveolens as a promising resource for antibiotic discovery.